Perbandingan Unjuk Kerja Purwarupa PLTS Apung dan PLTS Ground Mounted Menggunakan Sistem Monitoring Berbasis Internet of Things (IOT) - NKN Wulandari; IKPT Abinanda; INS Kumara; IW Sukerayasa; IAD Giriantari (VISA: Journal of Vision and Ideas, 2025)
This study examines the performance comparison between floating photovoltaic (FPV) systems and Ground Mounted solar power plants using an Internet of Things (IoT)-based monitoring system centered on the ESP32 microcontroller. The analyzed performance parameters include thermal and electrical factors: solar irradiance intensity, panel temperature, voltage, current, and output power. Data collection was conducted at the Faculty of Engineering, Udayana University, during June–July 2025, with observations taken between 10:00 AM and 2:00 PM Central Indonesia Time at 30-minute intervals. Measurements reveal that the panel temperature of the floating PV system consistently remains 1–4°C lower than that of the Ground Mounted system under equivalent irradiance conditions. This temperature difference influences power loss due to thermal effects, where the floating system experiences comparatively smaller power reductions than the Ground Mounted. After correcting for temperature factors, the floating PV output power was found to be higher at all observation times compared to the Ground mounted PV. These results demonstrate that the floating system exhibits superior thermal efficiency and electrical performance. The analysis confirms that implementing floating PV has significant potential to enhance energy conversion efficiency through natural cooling mechanisms, while also providing a strategic alternative for solar energy utilization in regions with adequate water resources.